Systems of computer algebra in mathematical logic - Бедратюк, Ганна Іванівна (Eastern-European Journal of Enterprise Technologies, 2012)
A description of the commands for the logic package of the computer algebra system Maple are given. The methods of solving some common mathematical logic problems with Maple are considered